Longitudinal, mixed method study to look at the experiences and knowledge of non melanoma skin cancer from diagnosis to one year - Bath-Hextall, Fiona; Jenkinson, Claire; Kumar, Arun; Leonardi-Bee, Jo; Perkins, William; Cox, Karen; Glazebrook, Cris (BioMed Central, 2013)
Background Skin cancer is the most common type of cancer in humans and the incidence is increasing worldwide. Our objective was to understanding the needs, experiences and knowledge of individuals with Non Melanoma Skin Cancer (NMSC) from diagnosis up until one year.